Effect of Stakeholders’ Engagement on Performance of Construction Projects in Rwanda: Case of Horizon Construction Company - Mukakarisa, Claudine; Njoroge, Naomi (International Journal of Entrepreneurship and Project Management, 2024)
Purpose: This research focused on the evaluation of the impact of stakeholder engagement on the performance of construction projects in Rwanda. The following specific objectives directed this study: to identify the impact of stakeholders' involvement in project planning on the performance of Horizon Construction Company's construction projects; to assess the impact of stakeholders' engagement in project implementation on the performance of Horizon Construction Company's construction projects; and to evaluate the impact of stakeholders' engagement in monitoring and evaluation on the performance of Horizon Construction Company's construction projects. Methodology: A combination of descriptive and correlational research survey design under a mixed method approach was used to guide the study. Participants in this research consisted of 182 individuals from Horizon Construction Company. Using stratified simple random sampling, this research sampled 125 people. A statistical Package for Social Sciences (SPSS) version 25 was used to analyze quantitative data along with thematic for qualitative data. Findings: The coefficient for stakeholders in project planning is 0.325, suggesting that for each unit increase in stakeholder engagement during the planning phase, project performance is expected to increase by 0.325, with this relationship being statistically significant (β = 0.325, t = 6.153, Sig. = 0.000). Similarly, the coefficient for stakeholders in project implementation is 0.268, indicating that a one-unit increase in engagement during implementation correlates with a 0.268 increase in project performance, which is also statistically significant (β = 0.268, t = 5.841, Sig. = 0.000). Additionally, the coefficient for stakeholders in monitoring and evaluation is 0.409, revealing that improvements in stakeholder engagement in oversight can enhance project performance by 0.409 units, with a statistically significant impact (β = 0.409, t = 8.030, Sig. = 0.000). Unique Contribution to Theory, Practice and Policy: it is recommended that Horizon Construction Company prioritize inclusive stakeholder engagement practices throughout all project phases.